How does embracing an outdoor lifestyle and sense of responsibility impact plastic reduction efforts? - Riordan, Oliver; Richter, Isabell (Frontiers in Sustainability, 2024)
Plastic pollution in coastal areas presents significant environmental challenges. This study investigates if an individual's outdoor lifestyle, and their views on entities responsible for litter management (governments, businesses, non-governmental organisations, Cornwall council and volunteers) affects their participation in plastic reducing activities. The study, focusing on 972 respondents from Cornwall, UK, measured peoples' perceptions, and behaviour around plastic reducing initiatives via survey questionnaires. Ten binomial logistic regression tests were run, one for each plastic reducing activity. Results indicated that perceptions regarding who is responsible greatly influenced individual actions. Positive correlations were observed between seeing national governments, businesses, and volunteers as accountable and participating in activities, particularly those outdoors like beach cleanups. Conversely, attributing responsibility to Cornwall council and NGOs showed negative associations with some activities. Recommendations include governmental interventions, liaising with sports groups, and community-oriented social marketing.